Characterization of Tetragenococcus halophilus from Vietnamese fish sauce - Ha, Le Thanh; Trinh, Nguyen Nam; My Chau, Le Thi; Minh Tu, Nguyen Thi (Vietnam Journal of Science and Technology, 2019)
The intracellular aminopeptidase activities and volatile compound profile of isolated halophilic lactic acid bacteria Tetragenococcus halophilus was investigated. Tetragenococcus halophilus CH2-4 and CH6-2 exhibited highest aminopeptidase activities 2.2 U/mL toward Glutamic-pNA. Meanwhile T. halophilus CH6-1 and V7-2 showed highest aminopeptidase activities 1.4 U/mL toward Leucine-pNA.  The total 19 volatile compounds, including esters, alcohols, ketones, phenols, hydrocarbons and sulfur containing compounds were detected in fish broth inoculated with T. halophilus.T. halophilus CH6-2 produced most volatile compounds, 10/19 detected ones in this study.